Politik Hukum Kenotariatan terhadap Larangan Notaris Melaksanakan Jabatan di Luar Wilayah Jabatannya - Nabila Safitri (Jurnal Hukum Lex Generalis, 2025)
In this era there are still many notaries who do their jobs outside of their office area. The policy of notarial law and the legal ramifications of a notary performing official functions outside of his or her jurisdiction are the subjects of this research. Using a normative judicial lens, the research reveals that the Notary Law forbids notaries from performing their duties outside of their area of ​​office (Article 17 letter a) and that notaries are only allowed to have one office in their domicile (Article 19). The genuine deed's evidential force might dwindle to that of a private deed due to the legal ramifications.